2001
DOI: 10.1046/j.1442-2042.2001.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative activity, angiogenesis and nuclear morphometry in renal cell carcinoma

Abstract: Background: Prognostic parameters other than tumor stage and grade are essential for renal cell carcinoma (RCC) patients. This study was undertaken to determine the usefulness of cellular proliferation, angiogenesis and nuclear morphometry in predicting the biological aggressiveness of RCC.Methods: Surgical specimens of 70 patients with RCC were investigated by conventional histology, Ki-67 immunostaining and stereological assessment of angiogenesis and mean nuclear volume.Results: There was no difference in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
1
15
0
4
Order By: Relevance
“…In nephrectomy specimens of nonmetastatic RCC (Tannapfel et al, 1996;Aaltomaa et al, 1997;Kirkali et al, 2001;Rioux-Leclercq et al, 2001) and mRCC (Rioux-Leclercq et al, 2001), Ki-67 (MIB-1) labelling index (LI) has been demonstrated as an independent parameter of unfavourable prognosis.…”
mentioning
confidence: 99%
“…In nephrectomy specimens of nonmetastatic RCC (Tannapfel et al, 1996;Aaltomaa et al, 1997;Kirkali et al, 2001;Rioux-Leclercq et al, 2001) and mRCC (Rioux-Leclercq et al, 2001), Ki-67 (MIB-1) labelling index (LI) has been demonstrated as an independent parameter of unfavourable prognosis.…”
mentioning
confidence: 99%
“…It is known that in addition to melanoma, RCC belongs to tumors with a low incidence of p53 mutations compared to, e.g. prostate and bladder cancer (Haitel et al 2000, Kirkali et al 2001, Rioux-Leclercq et al 2000. The low p53 mutation in different cancers (Olivier et al 2002) and the low immunohistochemical staining of RCC tissue blocks for the p53 protein in studies (Haitel et al 2000, Rioux-Leclercq et al 2000 suggest that mutations in p53 result in an accumulation of the p53 protein.…”
Section: Incidence Of P53 Ki-67 and Cox-2 Expressionsmentioning
confidence: 99%
“…The incidence of p53-and Ki-67-positive expression in RCC tumors was low in RCC studies (Kankuri-Tammilehto et al 2010, Kirkali et al 2001, Haitel et al 2000, Rioux-Leclercq et al 2000. It is known that in addition to melanoma, RCC belongs to tumors with a low incidence of p53 mutations compared to, e.g.…”
Section: Incidence Of P53 Ki-67 and Cox-2 Expressionsmentioning
confidence: 99%
“…For most of solid tumours, microvessel density (MVD) correlates with poor prognosis. However, MVD remains a controversial prognostic predictor for RCC (Kirkali et al, 2001;Sabo et al, 2001a;Suzuki et al, 2001;Dekel et al, 2002;Kinouchi et al, 2003;Yildiz et al, 2008;Qian et al, 2009), a significant contributory factor being that blood vessels in RCC may be regarded as being monolithic in structure and function, which might not accurately reflect the functional diversity based on microvessel differentiation and location. Mature blood vessels are usually covered by pericytes, and pericyte coverage is regarded as an indicator of vascular maturation (Gerhardt and Semb, 2008).…”
Section: Hai-lun Zhan Xin Gao* Xiang-fu Zhou Xiao-yong Pu De-juanmentioning
confidence: 99%